2006
DOI: 10.1097/01.mph.0000212955.43350.bb
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of bcl-2, p53, and p21 waf1 Protein Expression on the Outcome of Pediatric Hodgkin Lymphomas

Abstract: In Argentina, lymphomas account for 13.6% of all pediatric tumors and 47% of them are Hodgkin lymphoma. Previous studies of lymphoma series have reported the expression of apoptotic and cell cycle proteins. Our aim was to study these markers in our pediatric patients and correlate them with their outcome. Immunohistochemical staining with monoclonal antibodies anti-p53, bcl-2, p21, and mdm2 were performed on formalin-fixed paraffin-embedded Hodgkin lymphoma lymph node biopsies from 54 pediatric patients. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
3
6
0
1
Order By: Relevance
“…Literature data on BCA are focused mainly on CD20 and correlate its expression to either worse, 40 neutral, 41,42 or better 43 survival rates compared with controls. The same holds true for Bcl2 and p53, which have been variably associated with prognosis 10,20,43‐49 . It is nonetheless noteworthy that the only available studies on pediatric populations are in line with our results, as they exclude any prognostic role for such markers 10,20 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Literature data on BCA are focused mainly on CD20 and correlate its expression to either worse, 40 neutral, 41,42 or better 43 survival rates compared with controls. The same holds true for Bcl2 and p53, which have been variably associated with prognosis 10,20,43‐49 . It is nonetheless noteworthy that the only available studies on pediatric populations are in line with our results, as they exclude any prognostic role for such markers 10,20 …”
Section: Discussionsupporting
confidence: 88%
“…Bcl2 was scored as positive if >10% of HRS cells had protein expression equal to or greater than the accompanying small lymphocytes 19 . p53 was scored as positive if >50% of neoplastic cells featured strong nuclear staining 20 . Immunohistochemical reactions were independently assessed by two pathologists (MP and ST), with excellent interobserver agreement ( k > 0.80).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 50% of pediatric HL patients express Bcl-2 [36], and this Bcl-2 positivity is associated with decreased EFS in low-risk patients, and unfavorable risk patients in multivariate analysis [36]. However, some reports suggested that Bcl-2 expression did not affect outcomes [24, 37], and thus the prognostic value of Bcl-2 expression in HL is unclear.…”
Section: Molecular and Genetic Prognostic Biomarkersmentioning
confidence: 99%
“…CD15 negativity was observed in 33.8% of the cases and no association with clinical presentation or survival (OS, 95% CD15+ and CD15−; FFS, 82% CD15+ vs. 80% CD15−) was found. Dinand et al 1 also found that CD15 negativity was associated with p53 negativity ( P = 0.009), leading them to suggest that CD15 expression would relate to H‐RS cell survival and that “p53 deregulation might have a role in the loss of CD15 antigen expression.” This statement is difficult to interpret, since it is accepted that detection, and not absence of p53 immunoexpression, indicates p53 deregulation 9. Moreover, no information on the percentage of tumor cells expressing p53 used to define positive and negative cases (cut‐off), was provided; the use of different cut‐off criteria is a recognized cause of the controversy about the prognostic value of p53 expression in different HL studies 10.…”
Section: Prognostic Value Of Cd15 Expression In Hodgkin Lymphomamentioning
confidence: 99%